Design of Warehouse Management Information System (Case Study: PT Total Teknologi Rekacipta) - Meilani, Difana; Fitra, Hadyan Zada (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
This study aims to design a warehouse management information system by implementing the 5S method to address the stock checking and item arrangement disorganization at PT Total Teknologi Rekacipta. Currently, the company conducts stock recording manually, resulting in poorly arranged items, ungrouped spare parts, lengthy stock-checking processes, and frequent data duplication. The 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) is applied to organize the warehouse area, supported by developing a web-based inventory information system using the Waterfall methodology. The system is developed using PHP and MySQL, featuring data input, storage location tracking, and photo documentation. Black box testing results show that all functional system requirements are met. This system enhances stock management efficiency and accelerates company decision-making processes. The implementation reduced stock checking time from 1–2 days to less than 1 minute and eliminated data duplication. While 5S and web-based inventory are well-known approaches, this study contributes a practical implementation model by combining warehouse organization through 5S as a preparatory step before digitalization. This stepwise approach can serve as a reference for small and medium enterprises seeking to improve their physical warehouse management and digital stock control practices.